Ebp1 regulates myogenic differentiation of myoblast cells via SMAD2/3 signaling pathway. (13th July 2017) - Yu, Minli; Wang, Huan; Liu, Zhen; Lu, Yinglin; Yu, Debing; Li, Dongfeng; Du, Wenxing
Abstract : Regulation of skeletal muscle development requires many of the regulatory networks that are fundamental to developmental myogenesis. ErbB3 binding protein‐1 ( Ebp1 ) is involved in the control of myoblasts development in chicken. However, the expression and biological functions of Ebp1 in the progress of myogenesis are unclear. This study focused on determining the effect of Ebp1 on myogenic proliferation and differentiation using a primary myoblasts culture model. Ebp1 was found to upregulate in proliferating myoblasts and decrease at the early stage of myogenic differentiation. The level of endogenous Ebp1 increased from E9 to E20 chicken leg muscles. Knockdown of Ebp1 had no effect on myoblasts proliferation. However, myogenic differentiation into multinucleated myotubes was significantly reduced. The mRNA and protein expression of MRFs was decreased when Ebp1 was knocked down. Downregulation of Ebp1, accompanied by elevated levels of pSMAD2/3, suggests that Ebp1 is involved in regulating myogenic differentiation via SMAD2/3 inhibition. The phosphorylation of SMAD2/3 was activated and the expression of MYOD and MYOG was reduced in Ebp1 knockdown myoblasts, but addition of LY2109761 (an inhibitor specified to SMAD2/3) blocked these effects. Collectively, these results indicate that Ebp1 promotes myoblast differentiation by inhibition of SMAD2/3 signaling pathway during chicken myogenesis. These data provide new insights into the biological role of Ebp1 in embryonic chicken skeletal muscle development. Abstract : The present study showed a novel regulatory role and physiological importance of Ebp1 on myogenic development by inactivating SMAD2/3 signaling pathway. The present study has further defined molecular mechanism leading to myogenesis, especially the signaling pathway that induces myogenic differentiation, which is also essential for skeletal muscle development.